1998
DOI: 10.1021/ja980443r
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure Studies on the Garnet Y3Al5O12 by 27Al Single-Crystal NMR Spectroscopy

Abstract: The capability of single-crystal NMR to extract crystal structure information is demonstrated by a 27 Al single-crystal NMR study of the garnet Y 3 Al 5 O 12 (YAG). By rotation of a YAG single crystal about three perpendicular axes 93 27 Al spectra have been acquired, resulting in the observation of 3132 resonance frequencies. These have been assigned to three tetrahedral and four octahedral aluminum sites. A thorough analysis of the magnitudes and relative orientations of the quadrupole coupling tensors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…In the Y 3 [17]. In particular, it was shown that in the Y 3-x Dy x Al 5 O 12 there is no substitutional ordering [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Y 3 [17]. In particular, it was shown that in the Y 3-x Dy x Al 5 O 12 there is no substitutional ordering [12].…”
Section: Resultsmentioning
confidence: 99%
“…One of the most informative methods for the study of the local structure of atoms in solid-state materials with a high sensitivity is a nuclear magnetic resonance (NMR). The YAG crystals were also investigated by the NMR technique [8][9][10][11][12][13]. Previous solid-state 27 Al NMR investigations of the YAG confi rm that in the Y 3 Al 5 O 12 crystals there are two different Al sites (octahedral and tetrahedral), whose difference in the 27 Al chemical-shift values enables the separation of the two contributions, which differ in the quadrupolar coupling constant C Q = e 2 qQ/h [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In (c) are shown the extracted slice together with the best fit tabulated chemical shift and quadrupolar interaction parameters extracted experimentally, compared with those calculated by DFT. The quadrupolar interaction parameters reported in Florian et al [61] and Vosegaard et al [62] were also included for comparison. Both spectra were acquired at 14.1 T and 60 kHz magic-angle spinning field cycle convergence of 10 −7 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…has played a critical role in the extraction of CS and Q tensors from SSNMR of quadrupolar nuclei, and over 100 publications have cited their studies in the SSNMR field. In addition, over the past few decades, considerable efforts have been devoted to the development of techniques for extracting CS and Q tensors from powder and single‐crystal NMR spectra . Although there has been a strong impact on the SSNMR field, it appears, however, that errors in the single‐crystal NMR parameters (although NMR parameters for the two crystallographically equivalent cesium ions should be the same within experimental errors, only two digits are significant.…”
Section: Introductionmentioning
confidence: 99%